Polarimetric SAR Applications of Sea Ice: A Review - Mohammed Shokr; Mohammed Dabboor (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
Fully polarimetric (FP) and compact polarimetry (CP) modes are advanced technologies of synthetic aperture radar (SAR). Compared to the parameters available from traditional orthogonal backscatter coefficients, these technologies offer extra parameters, called polarimetric parameters, that fully characterizes the polarization status and the phase shift of the received backscattered signal. They include a set of ratios and correlation between co- and cross-polarization, with phase included, and another set of total backscatter power (SPAN) decomposed into power from each scattering mechanism (single-, multiple-, and double-bounce). Recent studies have demonstrated the potential of using polarimetric parameters in improving retrieval of snow and sea ice information. This review paper presents a brief background on polarimetric parameters available from the FP and CP modes and highlights their uses in applications of sea ice classification, concentration, surface features (rafting and ridging), new ice versus open water identification, thickness of thin ice, and multiyear ice surface discrimination between hummocks and melt pond. The potential of using power from the three scattering mechanisms is demonstrated in a few applications. Some information retrieved using polarimetric data cannot be retrieved using conventional SAR backscatter. This review concludes with a brief presentation on operational use of SAR polarimetric data (FP and CP) in operational ice monitoring programs.